Variability of the chemical composition of the wood and bark of two tropical hardwoods from Ghana - Kwaku Antwi; Francis Kofi Bih; Sylvia Adu; Joseph Appiah Yeboah (Les)
The study aims to investigate the chemical properties of the wood and bark of two tropical tree species Nesogordonia papaverifera and Holarrhena floribunda from Ghana to increase the efficiency of their utilization. For this purpose, for each of the species five mature trees with similar diameters at breast height were selected. Lignin, cellulose, hemicellulose, and total extractive content were determined from the sapwood and heartwood and bark of stems and branches of both species. The tests were conducted using the Technical Association of the Pulp and Paper Industry (TAPPI) standards. The lignin, cellulose, hemicellulose, and total extractive content vary along different locations in the stems and branches in both species. The sapwood generally had higher cellulose and hemicellulose content, while the heartwood and bark had a greater amount of lignin and extractives. This may affect the lower durability of sapwood. This study shows that heartwood of both Nesogordonia papaverifera and Holarrhena floribunda can be considered a source of value-added compounds.